The Challenges Confronting Computerized Health Records System Performance of the Pentecost Hospital, Accra: A Qualitative Study - Botchwey, Charles Owusu-Aduomi (European Scientific Journal, ESJ, 2022)
Background: Despite the use of computerized health records systems, its application is fraught with several obstacles, which slow down the pace of operations in Pentecost Hospital in Accra in Ghana. Aim: This study was designed to identify the challenges confronting the Computerized Health Records System performance of the Pentecost Hospital in Accra in Ghana. Methodology: The study espoused a qualitative method with a case study design through a well-structured interview guide and focus group discussions. In all, forty-five (45) respondents including ten (10) principal informers who were purposely selected due to their interest in the performance of the Computerized Health Records System at the Pentecost Hospital in the La Nkwantanang Madina Municipality took part in the study. Results and discussion: The study found that the introduction of the computerized health records system was faced with several challenges and they included inadequate knowledge about computerized health records systems, the breaks in internet connections of the systems, and the like. Recommendation: Effective monitoring mechanisms, provision of adequate financial and economic resources and the involvement of all the stakeholders in providing quality and efficient computerized health record systems as well as the provision of adequate training are key recommendations for improving the performance of the system. Conclusion: It is good to mention that efficient application of a computerized health record system which is geared towards efficient quality healthcare would flourish when parity, effectiveness, efficiency, and responsiveness of resource utilization for quality healthcare are considered as the building blocks.